Classroom Talk: Model Komunikasi Pembelajaran Pasca Pandemi Covid-19 di IAIN Langsa - Rusli Rusli; Lahmuddin Lahmuddin; Rubino Rubino (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Post-Covid-19 had extra impacts on Indonesian education. Learning activities experienced an evolution from offline to online, which is still happening today. Each college and university is under to move to online learning models; only a select number adopt hybrid learning, which blends offline and online learning methods. The quality of knowledge transfer supplied by lecturers to their students is significantly impacted by the online learning model, particularly in practical courses that rely upon close teacher-student interaction, and for students to receive and understand information transfer effectively, good communication patterns are required. This research aims to evaluate and identify the best communication model for learning in the post-COVID-19 pandemic environment. This study uses qualitative descriptive methods to describe and analyze the current learning communication model at IAIN Langsa, particularly in practical courses. This study used a phenomenological approach to observe phenomena that occur during online instruction at the IAIN Langsa campus. According to the findings of this study, virtual interactive communication patterns can boost students' curiosity, motivation, and interest in following and understanding the material offered. Communication with a model like this can help pupils improve their online learning abilities, because it requires students' active participation, virtual interactive communication can effectively message lecture materials.